2018
DOI: 10.1200/jop.18.00181
|View full text |Cite|
|
Sign up to set email alerts
|

Understanding the Role of Advanced Practice Providers in Oncology in the United States

Abstract: We identified 5,350 oncology APPs and conclude that number may be as high as 7,000. Survey results suggest that practices that incorporate APPs routinely rely on them for patient care. Given the increasing number of patients with and survivors of cancer, APPs are important to ensure access to quality cancer care now and in the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
82
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(86 citation statements)
references
References 8 publications
1
82
0
Order By: Relevance
“…Evidence from the development of nonphysician prescribing demonstrates that NPs prescribe appropriately in a wide range of clinical settings and that both patients and medical staff have positive views on these initiatives . Successful examples of NPs practicing in high‐acuity and hematology/oncology‐based clinical areas have been reported, and the number of NPs practicing in these areas is growing . Minimal knowledge exists of the competency of NPs to exercise the scope to prescribe transfusions specifically.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence from the development of nonphysician prescribing demonstrates that NPs prescribe appropriately in a wide range of clinical settings and that both patients and medical staff have positive views on these initiatives . Successful examples of NPs practicing in high‐acuity and hematology/oncology‐based clinical areas have been reported, and the number of NPs practicing in these areas is growing . Minimal knowledge exists of the competency of NPs to exercise the scope to prescribe transfusions specifically.…”
Section: Discussionmentioning
confidence: 99%
“…Nurse practitioners (NPs) in multidisciplinary care teams prescribing transfusions are increasingly common in clinical areas including hematology‐oncology, medical oncology, and the intensive care unit . Over 5000 advanced practice providers (APPs) in the United States, mostly composed of NPs, practice in oncology, and many states allow NPs to practice with full autonomy . However, there is a paucity of educational resources aimed at NPs, and little is known about the knowledge and competency of NPs to practice transfusion after their initial training educational curricula and practicums …”
mentioning
confidence: 99%
“…The American Society of Clinical Oncology (ASCO) conducted a cancer workforce survey in 2015 and estimated the NP workforce at 2700 and the PA workforce at 1100 individuals . A more recent collaboration in 2017, of the Oncology Nursing Society, ASCO, and the Association of Physician Assistants in Oncology identified 3623 NPs and 1796 PAs . These numbers are lower than our findings, which identified 4806 NPs and 3767 PAs in the SEER‐Medicare data alone.…”
Section: Discussionmentioning
confidence: 99%
“…We compared the routine activities of OPs [1] to those of NPs and PAs [12]. From the activity lists in the two studies, we only compared those activities performed by ≥ 80% of either group.…”
Section: Methodsmentioning
confidence: 99%
“…In 2007, it was estimated that NP/PAs could increase patient visits by 0.8 to 3.4 million by 2020 [2,3]. A more recent 2018 study updated the progress in incorporating NPs and PAs in oncology care teams noting that despite growth in both Advanced Practice Provider (APP) groups, a shortfall in projected patient visits persists [12]. This study identified 5350 APPs who were involved in cancer care and considered to be vital in ensuring access to quality patient care.…”
Section: Introductionmentioning
confidence: 99%